"Come on in North Side, you're just in time": Musical-Verbal Performance and the Negotiation of Ethnically Segregated Social Space - Scruggs, T. M. (Current Musicology, 2001)
Every Monday night in the 1970s and well into the 1980s jazz tenor sax-ophonist Von Freeman led his quartet, and a later open jam session, at the Enterprise Lounge on Chicago's Mrican American South Side.